Determinants of Bank Efficiency during Financial Restructuring Period: Indonesian Case - Felisitas Defung (University of Merdeka Malang, 2018)
The banking sector in Indonesia had been through many challenges aftermath the 1997 Asian financial crisis. The restructuring programs aimed to strengthen and improve the performance of the banking system. Empirical researches around the world, however, present various result with regard to the effect of the policy on bank efficiency. We investigated the determinants of the relative efficiency of the Indonesian banking industry. Using panel data of 101 Indonesian commercial banks, this study employs a non-parametric frontier method, Data Envelopment Analysis (DEA), to measure the efficiency score. In the second stage, the Tobit regression model used to analyse the factors that potentially determine the variation of efficiency score. The finding indicated the bank was technically inefficient particularly during financial restructuring. The improvement was evident toward the end of the period. Bank size, macroeconomic factors, and three bank groups were strongly associated with bank efficiency level. There was no strong evident that merger, which typically the form of restructuring policy output, positively associated with bank efficiency.JEL Classification: G21, G28, G34, C14DOI: https://doi.org/10.26905/jkdp.v22i3.2094